Glial Cell Contributions to Auditory Brainstem Development - Cramer, Karina S.; Rubel, Edwin W (Frontiers in Neural Circuits, 2016)
Glial cells, previously thought to have generally supporting roles in the central nervous system, are emerging as essential contributors to multiple aspects of neuronal circuit function and development. This review focuses on the contributions of glial cells to the development of auditory pathways in the brainstem. These pathways display specialized synapses and an unusually high degree of precision in circuitry that enables sound source localization. The development of these pathways thus requires highly coordinated molecular and cellular mechanisms. Several classes of glial cells, including astrocytes, oligodendrocytes and microglia, have now been explored in these circuits in both avian and mammalian brainstems. Distinct populations of astrocytes are found over the course of auditory brainstem maturation. Early appearing astrocytes are associated with spatial compartments in the avian auditory brainstem. Factors from late appearing astrocytes promote synaptogenesis and dendritic maturation, and astrocytes remain integral parts of specialized auditory synapses. Oligodendrocytes play a unique role in both birds and mammals in highly regulated myelination essential for proper timing to decipher interaural cues. Microglia arise early in brainstem development and may contribute to maturation of auditory pathways. Together these studies demonstrate the importance of non-neuronal cells in the assembly of specialized auditory brainstem circuits.